2021
DOI: 10.1007/s00436-021-07350-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in sex-specific abundance of the avian vampire fly (Philornis downsi)

Abstract: Understanding the range and behaviour of an invasive species is critical to identify key habitat areas to focus control efforts. Patterns of range use in parasites can differ temporally, across life stages and between sexes. The invasive avian vampire fly, Philornis downsi, spends the larval stage of its life within bird nests, feeding on developing nestlings and causing high levels of mortality and deformation. However, little is known of the ecology and behaviour of the non-parasitic adult fly life stage. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…N e was highest in 2006 and 2014 (but values for 2008 could not be obtained for the 10% missingness dataset), and lowest in 2020. Notably, this temporal decrease matches a decrease in mean in-nest P. downsi intensities (Common et al 2021) and daily catch rates of adult P. downsi across the sampling years (2014: 0.35 ± 0.03; Kleindorfer et al unpublished data;2020: 0.28 ± 0.02;Common et al 2022). The estimated values for effective population size were significantly smaller than expected, given the widespread distribution and high in-nest intensity of P. downsi.…”
Section: Effective Population Sizesupporting
confidence: 56%
See 1 more Smart Citation
“…N e was highest in 2006 and 2014 (but values for 2008 could not be obtained for the 10% missingness dataset), and lowest in 2020. Notably, this temporal decrease matches a decrease in mean in-nest P. downsi intensities (Common et al 2021) and daily catch rates of adult P. downsi across the sampling years (2014: 0.35 ± 0.03; Kleindorfer et al unpublished data;2020: 0.28 ± 0.02;Common et al 2022). The estimated values for effective population size were significantly smaller than expected, given the widespread distribution and high in-nest intensity of P. downsi.…”
Section: Effective Population Sizesupporting
confidence: 56%
“…Bait lure was replaced, and specimens were collected every seven days, for a total of seven trapping events. In 2020, 32 traps were placed every 50 m in a 200 m × 100 m lattice in two study plots, and along two 200 m transects in two separate plots (Common et al 2022). Traps were hung at four and seven metres high, to capture both male and female P. downsi, as previous research found a difference in capture height between the sexes .…”
Section: Field Sample Collectionmentioning
confidence: 99%
“…El Niño lowers marine productivity, and also has strong effects on terrestrial ecosystems [40] by changing rainfall patterns and plant productivity, and thus, exerting bottom-up effects on food webs including predator-prey interactions [41]. Parasite abundance is furthermore heavily influenced by precipitation [42,43] and a recent study on Floreana Island identified rainfall, proximity to human population and fruiting trees as the most important factors determining avian vampire fly abundance [44].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted the experiment in the lowlands and highlands on Santa Cruz Island and Floreana Island. All study areas have previously been part of long-term annual nesting monitoring of Darwin’s finch breeding biology monitored by our research group since 2000 (Common et al, 2022; Kleindorfer et al, 2021). Santa Cruz highland study plots were located in the Los Gemelos area (–0.625982, –90.384829), and the lowland study plots in the El Barranco area (0.739068, –90.301467).…”
Section: Methodsmentioning
confidence: 99%